Prevalence of high‐risk human papilloma virus among women with hepatitis C virus before liver transplantation. Issue 4 (6th May 2013) - Tarallo, P.A.; Smolowitz, J.; Carriero, D.; Tarallo, J.; Siegel, A.; Jia, H.; Emond, J.C.
Abstract: Background: We sought to assess the prevalence and risk factors for high‐risk human papillomavirus (HPV) infection among female liver transplant (LT) candidates. Traditional health screening before LT listing has included Pap smear and is typically carried out by the patient's local provider. The prevalence of high‐risk HPV in this population has not been studied. Methods: With Institutional Review Board approval, 62 LT candidates received a liquid‐based Pap smear with high‐risk HPV testing as part of their pre‐transplant evaluation by a single provider. Clinical variables included age, ethnicity, insurance status, prior Pap smear, and HPV results, HPV risk factors including age of first intercourse, number of lifetime partners, last sexual activity, smoking, birth control pill use, history of sexually transmitted infections, human immunodeficiency virus status, immunosuppressive medication, medical diagnoses, prescribed medications, and history of hepatitis A, B, C, or D. Results: The 62 women had a median age of 56 years, and 39% had high‐risk behavior known to be associated with HPV. Ten of 62 patients (16.1%) had high‐risk HPV at baseline screening, 5 of whom had atypical cytology. All of the patients who were positive for high‐risk HPV had an etiology of hepatitis C virus (HCV) as the underlying cause of liver disease, with the majority (90%) having no history of high‐risk behavior for HPV. In contrast, all patients with high‐risk behavior who were HCV negative were HPV negative. Fisher's exact test demonstrated a statistically significant relationship between HPV and HCV; odds ratio = 24.4, 95% confidence interval, 1.4, 438.7, P ‐value = 0.0013. None of the other potential risk factors were associated with HPV in this cohort. Conclusions: In this study, we provide evidence of a strong association between HCV and HPV in LT candidates, which has not been previously reported. HPV positivity was observed in non‐sexually active women, suggesting a reactivation of dormant HPV. An association between hepatitis C and high‐risk HPV could involve impairment of T‐cell function by hepatitis C. These data support close surveillance in women's health screening for LT candidates. Further studies to characterize immune responses in these patients will be in order.